Mani invisibili. Le trame provvidenziali del novel - Capoferro, Riccardo (Status Quaestionis, 2013)
This essay investigates the ontological and ideological implications of coincidences in the eighteenth- and nineteenth-century novel. In many canonical novels, coincidences were closely associated with providence and assumed a conservative meaning: propelling the plot, they replaced or reduced individual agency. At the same time, they re-enchanted the world by resurrecting “particular” providences, whose existence was questioned by increasingly rationalized forms of belief. The re-enchantment was, however, partial: poised between a modern view of the subject as a rational-empirical agent and a yearning for metaphysical underpinnings, novelists evoked the hand of God, but did not explicitly acknowledge its agency.